Biotope map of the German Baltic Sea. Issue 1 (15th July 2015) - Schiele, Kerstin S.; Darr, Alexander; Zettler, Michael L.; Friedland, René; Tauber, Franz; von Weber, Mario; Voss, Joachim
Highlights: We generate a full-coverage biotope map for the German Baltic Sea. The biotope map bases on the HELCOM HUB classification system. Full-coverage data on biological features is generated using predictive modelling. A consistent biotope map will facilitate marine management. Abstract: Full-coverage maps on the distribution of marine biotopes are a necessary basis for Nature Conservation and Marine Spatial Planning. Yet biotope maps do not exist in many regions. We are generating the first full-coverage biotope map for the German Baltic Sea according to the HELCOM Underwater biotope and habitat classification system (HUB). Species distribution modelling is applied to create full-coverage spatial information of biological features. The results of biomass modelling of twelve target taxa and presence/absence modelling of three target taxa enabled the identification of biological levels up to HUB level 6. Environmental data on bathymetry, light penetration depth and substrate are used to identify habitat levels. HUB biotope levels were combined with HUB habitat levels to create a biotope map. Altogether, 68 HUB biotopes are identified in the German Baltic Sea. The new biotope map combining substrate characteristics and biological communities will facilitate marine management in the area.